2014
DOI: 10.1002/cncr.28726
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus in combination with octreotide long‐acting repeatable in a first‐line setting for patients with neuroendocrine tumors: An ITMO group study

Abstract: BACKGROUND Preclinical and clinical studies suggest synergistic activity between somatostatin analogues and mammalian target of rapamycin inhibitors. The activity and safety of everolimus was assessed in combination with octreotide long‐acting repeatable (LAR) in patients with neuroendocrine tumors (NETs) of gastroenteropancreatic and lung origin. METHODS This was a phase 2, multicenter trial using a Simon's 2‐stage minimax design. Treatment‐naive patients with advanced well‐differentiated NETs of gastroentero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 33 publications
1
65
0
2
Order By: Relevance
“…Data on 50 naïve advanced NETs showed a single grade 4 AE in 1 patient and no report of grade 3-4 thrombocytopenia or pneumonitis [23].…”
Section: Discussionmentioning
confidence: 93%
“…Data on 50 naïve advanced NETs showed a single grade 4 AE in 1 patient and no report of grade 3-4 thrombocytopenia or pneumonitis [23].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, treatment duration with everolimus was longer for patients who were naïve to chemotherapy, thus suggesting that it was better tolerated in the chemonaïve group. The ITMO study group (Bajetta et al 2014) suggests that combined therapy with everolimus/octreotide LAR can be effective as the first line for patients with NETs. The two studies are obviously not comparable, both for the different sample size and for the design of the study.…”
Section: Discussionmentioning
confidence: 99%
“…They also specified that, among patients with pNETs, 2 partial responses (PR) were observed, while none showed a complete response (CR). As for the secondary endpoints [Time To Progression (TTP), and Overall Survival (OS)], no significant differences were observed after a median of 227 days (Bajetta et al 2014). Even with the limitations of the study, such as the low number of subjects and the lack of a control group, the ITMO study Group suggests that combined therapy with everolimus/octreotide LAR can be effective as first line for patients with pNETs as well as with NETs of other origin.…”
Section: Published Prospective Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent multicenter Italian study on the compassionate use of everolimus in advanced NETs highlighted the increasing risk of severe toxicity in patients who had been previously treated with PRRT or chemotherapy, thus suggesting the early use of everolimus in patients with advanced NETs. [22] Furthermore, Bajetta et al [23] treated patients with everolimus in combination with octreotide LAR as first line approach in advanced NETs and showed that in this setting, this combination treatment is very effective with disease control being reached in 92% of patients. This therapy also has an excellent safety profile, with only one single grade 4 adverse event in the population of 50 patients enrolled.…”
Section: Peptide Receptors Radionuclide Therapy (Prrt)mentioning
confidence: 99%